2013
DOI: 10.1103/physrevd.88.064020
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic models for globular clusters, Galactic bulges, and dark halos

Abstract: Spherical systems with polytropic equations of state are of great interest in astrophysics. They are widely used to describe neutron stars, red giants, white dwarfs, brown dwarfs, main sequence stars, galactic halos, and globular clusters of diverse sizes. In this paper we construct analytically a family of self-gravitating spherical models in the post-Newtonian approximation of general relativity. These models present interesting cusps in their density profiles which are appropriate for the modeling of galaxi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 152 publications
1
34
0
1
Order By: Relevance
“…[17][18][19][20][21][22][23][24][25] (and references therein for an extensive discussion on this point).…”
Section: Introductionmentioning
confidence: 99%
“…[17][18][19][20][21][22][23][24][25] (and references therein for an extensive discussion on this point).…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24][25][26][27][28][29][30][31][32], and references therein for an extensive discussion on this point).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies on the properties of anisotropic star can be found for examples in Refs.1-2 while studies for other anisotropic configurations can be found in Refs. 45,[47][48][49]. These studies reveal that anisotropy may have effects on maximum equilibrium mass and gravitational redshift.…”
Section: -19mentioning
confidence: 99%